Da porteira para dentro: as práticas lusitanas nas transformações do rural e no fazer turístico da Microrregião de Viçosa-MG - Tiradentes, Leomar (2010)
In this study we analyzed the activities of tourist Viçosa - MG. We identified the content and process of landscape construction and development of this region. Development and understanding as to how this content landscaped interact redefining the local area. We found an exploratory and qualitative nature; we use the case study as a methodology, with the instrument, the field work. Also, we use observation and semi-structured interviews. The aim of this study was to analyze the manifestations of tourism in rural areas, and their relationship to the way of life, place and landscape of rural properties in the micro region of Viçosa-MG. And we used as reference point, the practices of rural tourism in the region of Minho (Portugal). The results indicated that tourism activities are within the reality of these properties. Overall, tourism in rural areas is, in the farms surveyed, a place historically constituted for agricultural production as its uses and appropriations will allow their owners to do a tour full of peculiarities. The results indicated that tourism activities are within the reality of these properties. Overall, tourism in rural areas is, in the farms surveyed, a place historically constituted for agricultural production as its uses and appropriations will allow their owners to do a tour full of peculiarities.